Improving antibiotic prescribing for community-acquired pneumonia in a provincial hospital in Northern Vietnam. Issue 2 (17th May 2021) - Do, Nga T T; Li, Ryan; Dinh, Huong T T; Nguyen, Huong T L; Dao, Minh Q; Nghiem, Trang N M; Nadjm, Behzad; Luong, Khue N; Cao, Thai H; Le, Dung T K; Cluzeau, Francoise; Ngo, Chau Q; et al.
Abstract: Objectives: To test the effectiveness of a quality improvement programme to promote adherence to national quality standards (QS) for patients hospitalized with community-acquired pneumonia (CAP), exploring the factors that hindered improvements in clinical practice. Methods: An improvement bundle aligned to the QS was deployed using plan-do-study-act methodology in a 600 bed hospital in northern Vietnam from July 2018 to April 2019. Proposed care improvements included CURB65 score guided hospitalization, timely diagnosis and inpatient antibiotic treatment review to limit the spectrum and duration of IV antibiotic use. Interviews with medical staff were conducted to better understand the barriers for QS implementation. Results: The study found that improvements were made in CURB65 score documentation and radiology results available within 4 h ( P  <   0.05). There were no significant changes in the other elements of the QS studied. We documented institutional barriers relating to the health reimbursement mechanism and staff cultural barriers relating to acceptance and belief as significant impediments to implementation of the standards. Conclusions: Interventions led to some process changes, but these were not utilized by clinicians to improve patient management. Institutional and behavioural barriers documented may inhibit wider national uptake of the QS. National system changes with longer term support and investment to address local behavioural barriers are likely to be crucial for future improvements in the management of CAP, and potentially other hospitalized conditions, in Vietnam.